(untitled) (Journal of the College of Education for Women, 2019)
King Ghazi (1933-1939) was of the Arabic characters that characterized national andpatriotic spirit and that faced the British policy in all its aspects.King Ghazi distinguished as of Arab nationalist tendencies and called for theliberalization of Arab lands which were under the rule of the Ottoman Empire. He called forreunification under the one Arab country, Hence came the King invitations to liberate Kuwaitfrom the British protectorate and consolidated with Iraq.King Ghazi established a private radio station in the royal palace (AL zzaahoor) palaceand provided special programs to return of Kuwait to Iraq, this radio station was Theprominent role in the revitalization of the Kuwaiti National Movement, and invitation thecontinuous to accession of Kuwait to Iraq. In front of the unjust verdicts issued by the ruler ofKuwait, and happened a big demonstrations appealed to King Ghazi to move quickly to joinKuwait to Iraq.The policy of King Ghazi caused concern to the British embassy in Iraq and then theBritish Government, that the British influence was imposing control in each of thedepartments of the states and in the army, so the British officials realized that the presence ofthe king became a threat to their interests, which prompted the British Ambassador (MorrisPeterson ) to make a statement publicly when he left Baghdad in March 1939, saying that "theKing Ghazi, must be controlled or thrown off."